Rural space in the Middle Ages and early modern age : the spatial turn in premodern studies - Classen, Albrecht (Fundamentals of medieval and early modern culture ;, 2012)
"Older research on the premodern world limited its focus on the Church, the court, and, more recently, on urban space. The present volume invites readers to consider the meaning of rural space, both in light of ecocritical readings and social-historical approaches. While previous scholars examined the figure of the peasant in the premodern world, the current volume combines a large number of specialized studies that investigate how the natural environment and the appearance of members of the rural population interacted with the world of the court and of the city. The experience in rural space was important already for writers and artists in the premodern era, as the large variety of scholarly approaches indicates. The present volume signals how much the surprisingly close interaction between members of the aristocratic and of the peasant class determined many literary and art-historical works. In a surprisingly large number of cases we can even discover elements of utopia hidden in rural space. We also observe how much the rural world was a significant element already in early-medieval mentality. Moreover, as many authors point out, the impact of natural forces on premodern society was tremendous, if not catastrophic."--Publisher's website.